A new species of Chusquea subg. Chusquea (Poaceae—Bambusoideae—Bambuseae) from Minas Gerais, Brazil: morphological evidence and phylogenetic placement within the Euchusquea clade - Vidal, Kaio Vinicius De A.; Welker, Cassiano A. Dorneles; Oliveira, Iasmin Laiane C.; Mota, Aline Costa Da; Oliveira, Reyjane P.; Clark, Lynn G. (Phytotaxa, 2018)
Chusquea gouveiensis is a new species of tropical woody bamboo from Brazil, herein described and illustrated. It is classified within C. subg. Chusquea, mainly based on its scandent habit, triangular central bud with vertical orientation, extra-or infravaginal branching, and lemma margins free at the apex. The new species is most similar to C. gracilis because they share culm leaves with undifferentiated sheaths and blades with a folded or twisted apex, and foliage leaves and spikelets of similar length. However, C. gouveiensis is distinguished from C. gracilis by having branch complements of 40‒90 usually ascending subsidiary branches (vs. 70‒195 mostly horizontally oriented subsidiary branches), synflorescences weakly paniculate to racemose (vs. paniculate), glumes I and II collectively 0.3‒0.7 mm long (vs. 0.1‒0.2 mm long), and glumes III and IV awned and abaxially pilose to pubescent at the apex (vs. mucronate and glabrous). The two species also differ in distribution: C. gouveiensis is only known from the region of Gouveia and Diamantina, in the southern portion of the Espinhaço Range in Minas Gerais state, Brazil, in forest fragments at 1,200‒1,300 m.a.s.l., whereas C. gracilis occurs in the southern Brazilian states of Paraná, Santa Catarina and Rio Grande do Sul, in mixed ombrophilous forests between 550 and 880 m.a.s.l. Based on nuclear internal transcribed spacer (ITS) and plastid DNA sequence data (ndhF and trnD-trnT), a sixth lineage within the Euchusquea clade was identified, herein named clade VI—Chusquea meyeriana clade, comprising a significant portion of the Brazilian species of Chusquea. The new species has phylogenetic affinities with the C. meyeriana informal group and is also distinct from C. gracilis in the phylogeny.